Pemberdayaan Paguyuban “Watubonang” dalam Meningkatkan Pelayanan Wisata Alam Ngeliban dengan Model BRANTAS - Kusumawijayanti, Anita Reta; Primasari, Yusniarsi; Lestanti, Sri; Susanti, Laili Neni; Mahmudi, Salsa Billa Dewi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
This Community Service Activity (PKM) aims to empower the Watubonang Community as the implementer of Ngeliban natural tourism in Minggirsari Village, Blitar Regency in improving Ngeliban natural tourism services through the implementation of the Sustainable, Environmentally Friendly, Local Wisdom, Traditional, and Social Media Awareness (BRANTAS) Model. This model integrates various aspects of community empowerment, including training, resource management, and social media-based promotion of natural tourism. The service implementation method involves a participatory approach by actively involving community members in each stage of model implementation, including 1) socialization and training on the BRANTAS ecotourism model, 2) Video Content Creation Training, and 3) Digital Marketing Training. The PKM results show that the implementation of the BRANTAS Model has succeeded in improving the quality of tourism services by increasing the product knowledge of ngeliban tour guides as indicated by the results of the training questionnaire responses which are quite good, 97% understand the BRANTAS ecotourism model. This activity has also increased community participation in promotions via social media, as demonstrated by the increase in Minggirsari village Instagram followers from 1179 to 1221 followers. In conclusion, this PKM was able to have a positive impact on the Watubonang community of Minggirsari Village, Blitar Regency, and the BRANTAS model can be a reference for developing nature-based tourism in other areas.